Показательное уравнение
Задание номер три

Показательное уравнение
Задание номер три

14-09-2019 02:03 Просмотры: 1
Ответы (1)
Севрин Смычук
+9
2019-09-14 03:19:54

Заметим, что (2+√3)(2-√3)=4-3=1⇒2-√3=1/(2+√3). Домножим уравнение на (2-√3) (2-√3)(2+√3)(2+√3)^(x^2-2x)+(2-√3)^(x^2-2x)=4;     (2+√3)^(x^2-2x)+(2-√3)^(x^2-2x)=4;     (2+√3)^(x^2-2x)+(1/(2+√3))^(x^2-2x)=4; (2+√3)^(x^2-2x)=t; t+1/t=4;  t^2-4t+1=0; t=2+√3 или t=2-√3; в первом случае  (2+√3)^(x^2-2x)=(2+√3)^1;  x^2-2x=1; x^2-2x-1=0;  x=1+√2 или x=1-√2; во втором случае    (2+√3)^(x^2-2x)=2-√3; (2+√3)^(x^2-2x)=(2+√3)^(-1); x^2-2x= -1; (x-1)^2=0; x=1 Ответ:  1+√2; 1-√2; 1